Una nueva visión de la naturaleza económica y jurídica de los intereses en el Código Civil peruano - Ayllón Valdivia, César Arturo (2024)
It is precisely the lack of consensus in the civil doctrine, which mostly assimilates interests as ‘civil fruits of capital’, which drew our attention to the study of the latest contributions of economic doctrine. In this work, through the dogmatic method, limited to a brief analysis for publication reasons, we intend to identify the meeting points between economic and legal doctrine about the concepts of interest and capital. Then, we will show some of the problems presented by the distinction between compensatory and moratorium interest in the peruvian Civil Code. Finally, we will conclude that the money-rate of interest is the one that must be applied to the payment for the disposition of the money capital whose determination obeys the rules of the free market.